Managing Pregnant Women with Hemophilia and von Willebrand Disease: How Do We Provide Optimum Care and Prevent Complications? - Janbain M; Kouides P (Dove Medical Press, 2022)
Maissaa Janbain,1 Peter Kouides2 1Deming Department of Internal Medicine, Section of Hematology and Medical Oncology, Tulane School of Medicine, New Orleans, LA, USA; 2Department of Medicine, University of Rochester School of Medicine and Dentistry, Rochester, NY, USACorrespondence: Maissaa Janbain, Deming Department of Internal Medicine, Section of Hematology and Medical Oncology, Tulane School of Medicine, 1430 Tulane Ave 8078, New Orleans, LA, 70112, USA, Tel +15049888840, Fax +15049888843, Email mjanbain@tulane.eduAbstract: The challenge of pregnancy can be significant to the point of being life-threatening in a woman with a bleeding disorder. Additionally there can be a risk to the fetus and the neonate. A hemostatic defect can affect the course of the pregnancy, but the impact is most feared around delivery in the immediate and the extended post partum period, requiring rapid identification and prompt referral to a hematologist for assistance in management. Identifying the type of congenital bleeding disorder and knowing its inheritance pattern is crucial during counseling prior to conception and in preparation for delivery. A comprehensive approach by a specialized and experienced team in a tertiary care center with access to adequate laboratory monitoring and therapies can facilitate the process. The multidisciplinary team should include a hematologist, an obstetrician, a pediatric hematologist, an anesthesiologist, and in select cases a clinical geneticist and a maternal fetal medicine specialist. In this review article, we will detail the diagnostic path and management of pregnancy and delivery in women with some inherited bleeding disorders, in particular those affected by hemophilia A (HA), hemophilia B (HB), and von Willebrand disease (VWD).Keywords: pregnancy, hemophilia A and B carriers, von Willebrand disease, delivery